PENGEMBANGAN DESAIN KEMASAN PADA UKM AMANDA BROWNIES - Sanjaya; Sri Zetli (LPPM Universitas Putera Batam, 2025)
This study alims to analyze consumer standards for Amanda Brownies product packaging using the BackMarking and House of Quality methods. The results of the study indicate that there are 19 criteria that are consumer standards for the product packaging. In competitor analysis, BackMarking identified the malin competitors in the Amanda Brownies UKM product packaging category. Based on the results of the House of Quality analysis, the normalized ralw weight value shows the grealtest demand from consumers regarding Amanda Brownies packaging design, with al value range between 0.013. Several criteria that are consumer priorities in packaging design are Attractive Packaging Shape (B1), Packaging that Displays Expiration Date Clearly (B7), Packaging Material Thickness (B16), and Packaging that Displays Slogan/Tagline (B19). In designing packaging products, the technical elements that are the malin priority are Letter Color Variants (Priority 1), Writing Font Dimensions (Priority 2), Color Variants (Priority 3), and Tagline Description (Priority 4). These findings provide important insights for the development of Amanda Brownies product packaging that suits consumer needs and preferences.